Novel fluorescent perylene liquid crystal with diphenylacrylonitrile groups: Observation of a large pseudo stokes shift based on AIE and FRET effects. (December 2017) - Zhu, Mingguang; Zhuo, Youzhen; Cai, Kaicong; Guo, Hongyu; Yang, Fafu
Abstract: A novel perylene liquid crystal with diphenylacrylonitrile groups on 1, 7-bay positions was synthesized in high yield. This highly decorated perylene bisimide showed the ordered hexagonal columnar liquid crystalline behaviour between 124.9 and 189.5 °C. Upon excitation of 480 nm, an attenuation of fluorescent intensity was observed with the increase of water fraction in THF/H2 O mixtures. However, the fluorescence intensity enhanced dramatically and attained a maximum value at water fraction of 40% in THF/H2 O systems when excited at 330 nm. The fluorescence intensity increased by 10 times and the pseudo Stokes shift achieved 251 nm. These phenomena were well elucidated by the AIE and FRET effect, which were supported by the investigation of fluorescence quantum yield and fluorescence lifetime. Graphical abstract: Highlights: Novel perylene liquid crystal with diphenylacrylonitrile groups was synthesized. It showed the ordered hexagonal columnar mesophase. Its fluorescence increased in THF/H2 O mixtures when excited at 330 nm. The pseudo Stokes shift was as large as 251 nm. The AIE and FRET effect was firstly observed for perylene liquid crystal.